Captura de carbono en sistema agroforestal de cacao (Theobroma cacao L.) como medida de mitigación al cambio climático. Platanales, Bolívar, Manabí - Solórzano Álava, Tairun Francisco (2025)
The research evaluated carbon sequestration in a cacao (Theobroma cacao L.) agroforestry system as a climate change mitigation measure. First, the species present in the system were quantified through direct observation, and then the stored carbon was estimated using a non-destructive allometric method. Based on the results, strategies aimed at strengthening mitigation capacity were proposed. The study recorded a diversity of 2,887 individuals belonging to different species, with cacao being the dominant species, representing 80.78%. Banana (Musa sp.), coffee (Coffea arabica), mango (Mangifera indica), orange (Citrus sinensis), and shade trees such as avocado (Persea americana), cedar (Cedrela odorata), and guachapelí (Schizolobium parahyba) were also identified. The evaluated agroforestry system stored between 4.68 and 6.88 tons of carbon per hectare, with an estimated annual carbon sequestration of between 17.19 and 25.23 tons of CO₂ per hectare. It was evident that plots with greater tree diversification had greater carbon sequestration capacity. Based on these findings, strategies such as the inclusion of timber and fruit species, the incorporation of shade trees, and technical training for producers were proposed. These results supported the capacity of cacao agroforestry systems to effectively capture carbon.